Density Depletions Associated With Enhancements of Electron Cyclotron Harmonic Emissions: An ERG Observation. Issue 19 (3rd October 2018) - Kazama, Y.; Kojima, H.; Miyoshi, Y.; Kasahara, Y.; Usui, H.; Wang, B.‐J.; Wang, S.‐Y.; Tam, S. W. Y.; Chang, T.‐F.; Ho, P. T. P.; Asamura, K.; Kumamoto, A.; et al.
Abstract: In this study, we describe small‐scale density depletions of cold electrons associated with electrostatic electron cyclotron harmonic (ECH) waves observed by the ERG (Exploration of energization and Radiation in Geospace) spacecraft during a plasmapause crossing near the magnetic equator in the postmidnight sector. The total electron density was roughly 2 orders of magnitude larger than that of the hot electrons, indicating existence of a cold and dense electron population below ∼20 eV. The cold electron density profile showed small‐scale density depletion regions, in which the ECH emissions were intensified. Moreover, a flux enhancement of hot electrons in the perpendicular direction was also associated with the ECH emissions intensity. This relation suggests perpendicular energization of electrons by electric field oscillation of the ECH waves. Plain Language Summary: This study clarifies a relation of cold‐electron density irregularities and electron cyclotron harmonic (ECH) waves, both of which are frequently observed in the inner magnetosphere but their relation had not been clearly indicated by observations. We analyzed a plasmapause crossing event on 12 April 2017 observed by the ERG spacecraft and found that the plasmapause had small‐scale density depletions of cold electrons and ECH emissions were intensified inside the depletion regions. This suggests that an ECH emission intensity can be controlled by a background cold‐electron population. In addition, enhancements of hot‐electron fluxes in the direction perpendicular to the local magnetic field were also observed in response to the ECH emissions. This is probably due to perpendicular energization of cold electrons by the oscillating electric field of the ECH waves. The close relation between cold electrons and ECH emission intensification, shown in this analysis, gives indication of leakage of ionospheric cold electrons and its control of equatorial ECH waves just outside the plasmapause. Key Points: The ERG spacecraft observes density depletions associated with ECH waves during a plasmapause crossing The ECH waves are intensified inside the density depletion regions The electric field of the ECH waves energizes electrons in the perpendicular directions